2014
DOI: 10.1038/onc.2013.568
|View full text |Cite
|
Sign up to set email alerts
|

A link between inflammation and metastasis: serum amyloid A1 and A3 induce metastasis, and are targets of metastasis-inducing S100A4

Abstract: S100A4 is implicated in metastasis and chronic inflammation, but its function remains uncertain. Here we establish an S100A4-dependent link between inflammation and metastatic tumor progression. We found that the acute-phase response proteins serum amyloid A (SAA) 1 and SAA3 are transcriptional targets of S100A4 via Toll-like receptor 4 (TLR4)/nuclear factor-κB signaling. SAA proteins stimulated the transcription of RANTES (regulated upon activation normal T-cell expressed and presumably secreted), G-CSF (gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 47 publications
7
125
1
3
Order By: Relevance
“…The secretion of S100A4 by tumor and stromal cells is believed to serve as a key player in the metastasis of cancer cells or affecting angiogenesis. 28-30 Although we did not know which form of S100A4 plays more important roles in colon tumorigenesis, our IHC staining of colon tumors suggests the weak intracellular staining, and our functional studies support a major source of myeloid cell-producing S100A4 during colon cancer development. It is certainly also important to analyze the role of intracellular S100A4 in myeloid cells during the development of colon tumorigenesis in the future.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The secretion of S100A4 by tumor and stromal cells is believed to serve as a key player in the metastasis of cancer cells or affecting angiogenesis. 28-30 Although we did not know which form of S100A4 plays more important roles in colon tumorigenesis, our IHC staining of colon tumors suggests the weak intracellular staining, and our functional studies support a major source of myeloid cell-producing S100A4 during colon cancer development. It is certainly also important to analyze the role of intracellular S100A4 in myeloid cells during the development of colon tumorigenesis in the future.…”
Section: Resultsmentioning
confidence: 70%
“…21 , 29 , 30 To test whether S100A4 is secreted by S100A4 + cells in the CRC tissue, CD11b + S100A4 + cells were isolated from DSS-treated colon tissues and were cultured in vitro, and the supernatant was analyzed for S100A4 by ELISA. CD11b + S100A4 − cells were used as control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, Oh et al (41) reported 929 significant epithelial-stromal coexpression interactions among 11,700 ϫ 11,700 ϭ 136,890,000 pairwise associations tested in normal breast tissue. Interestingly, all the top detected genes have been implicated in the link between inflammation and cancer of the colon (5,18,20,35,39,44,46,49,56,62). Additional systems-level analyses on independent RNA-Seq data sets are needed to further explore how colonic stromal and epithelial interactions temporally evolve during malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Both endogenous and extracellular S100A4 have been linked to metastasis. Endogenous S100A4 is known to enhanced cell motility and invasion (Grundker et al ., 2016), while extracellular, stromal S100A4 has been shown to instigate inflammatory events promoting metastasis (Hansen et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%